PRINSIP KEADILAN DALAM PELAKSANAAN PERATURAN DI BIDANG KETENAGALISTRIKAN TERHADAP PIHAK SWASTA DALAM USAHA PENYEDIAAN TENAGA LISTRIK - Suryani (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
Article 33 paragraph (2) and paragraph (3) of the 1945 Constitution of the Republic of Indonesia regulates guarantees for the exploitation of electricity supply which is controlled by the state which is used for the maximum prosperity of the people. However, in an effort to increase the country's ability to supply electricity, the government provides opportunities for private business entities, cooperatives and non-governmental organizations to participate in the electricity supply business. Problems arise when there is a PT PLN (Persero) policy that limits the rights of private actors in supplying electricity. The problem in this study is how is the principle of justice in the implementation of regulations in the electricity sector towards private parties in the business of providing electricity? The research method used is normative juridical. The results of the study reveal that the principle of justice in the implementation of regulations in the electricity sector towards private parties in the business of supplying electricity is contrary to the principle of distributive justice. The actions of PT PLN (Persero) regarding making it difficult for the installed power capacity of the development of rooftop PLTS to a maximum of 15% in several regions are inseparable from the Indonesian ideology which is based on nationalist understanding which is more concerned with domestic interests. If PT PLN (Persero) could pay attention to the Constitutional Court Decision Number 111/PUU-XIII/2015 which states that the phrase